2021
DOI: 10.1002/ardp.202000470
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and anticancer activity of ethyl 5‐amino‐1‐N‐substituted‐imidazole‐4‐carboxylate building blocks

Abstract: A series of 5‐amino‐1‐N‐substituted‐imidazole‐4‐carboxylate building blocks was synthesized and assayed for their antiproliferative potential against human cancer cell lines, including HeLa (cervical), HT‐29, HCT‐15 (colon), A549 (lung), and MDA‐MB‐231 (breast) cells. The preliminary screening results revealed that several derivatives containing alkyl chains at the N‐1 position of the imidazole core demonstrate a certain inhibitory effect on growth and proliferation. A significant effect was observed following… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 33 publications
0
7
0
3
Order By: Relevance
“…In recent years, much information has been published about pyrimidine derivatives condensed with various heterocycles [12], such as: purines, pteridines, quinazolines, pyridopyrimidines, pyrimidoazepines, furo-and pyrrolopyrimidines, thienopyrimidines, their synthesis and chemical transformations. also confirm the importance of these class combinations [13][14][15][16]3,[17][18][19][20][21][22].…”
mentioning
confidence: 59%
See 3 more Smart Citations
“…In recent years, much information has been published about pyrimidine derivatives condensed with various heterocycles [12], such as: purines, pteridines, quinazolines, pyridopyrimidines, pyrimidoazepines, furo-and pyrrolopyrimidines, thienopyrimidines, their synthesis and chemical transformations. also confirm the importance of these class combinations [13][14][15][16]3,[17][18][19][20][21][22].…”
mentioning
confidence: 59%
“…The corresponding 3,1-oxazine-4-one (18) was obtained by its interaction with acetic anhydride and the 2-chloromethyl derivative ( 19) by its interaction with chloroacetyl chloride in the presence of triethylamine. The resulting 3,1-oxazine-4-ones (18,19) react with panisidine in a 1:1 and 1:2 ratio to give thieno [2,3-d]pyrimidine (20,21) containing alkyl and aryl groups in the expected 2 -and 3-positions: The corresponding thienopyrimidin-4-ones (23) were obtained by acylation and heating in acidic medium of the amino group in nitriles of 2-aminothiophene-3-carboxylic acid (22) containing various substituents in the 4,5-state [33]. 4-Iminothieno[2,3-d]-3,1-oxazines formed as intermediates in the reaction are redistributed into thienopyrimidine-4-ones (23).…”
Section: Synthesis and Reactions Of 2-n(alkylaryl)-thieno[23-d]pyrimi...mentioning
confidence: 99%
See 2 more Smart Citations
“…Compound 44 showed the best anticancer activity with HeLa, HT-29, A549, HCT-15, and MDA-MB-231 cell lines with IC 50 values of 0.81, 1.77, 15.22, 17.92, and 5.48 μM. Reference drug Doxorubicin presented IC 50 values of 0.1, 0.03, 1.1, 0.27, and 0.51 Μm, respectively [ 161 ]. Singh et al (2021) synthesized and reported C 6 -substituted benz[4,5]imidazo[1,2-α]quinoxaline derivatives and performed their anticancer evaluation.…”
Section: Current Advances In Nitrogen Containing Heterocycles As Anti...mentioning
confidence: 99%